Climate change adaptation: a study of multiple climate-smart practices in the Nile Basin of Ethiopia. (7th February 2019) - Teklewold, Hailemariam; Mekonnen, Alemu; Kohlin, Gunnar
Abstract : Improving farm-level use of multiple climate change adaptation strategies is essential for improving household food security, particularly against a backdrop of a high risk of climatic shocks. However, the empirical foundation for understanding how farm households choose multiple climate-smart practices is far from being established. In this paper, the effects of household, farm and climatic factors on farmers' decisions to use multiple adaptation practices are analysed. A survey of 921 farm households and 4312 farm plots combined with historical climate data in the Nile Basin of Ethiopia is explored using multivariate and random effect ordered probit econometric models. Results show agricultural production can be characterized by complementarities between adaptation practices. This result is important to designing packages of adaptation practices. The econometric results confirm that social capital, tenure security and climatic shocks are important determinants of the choice of the type and number of adaptation practices. The results suggest the need for carefully designing combinations of adaptation strategies based on agro-ecological conditions.